Motherhood Reflected in Veronica Roth's Divergent Novel (2011): A Feminist Perspective - Saputri, Devica Hilara Pingkan; , Dewi Candraningrum,Phil (2017)
This study aimed to describe motherhood main character happens to the novel Divergent (2011) by Veronica Roth by using the theory of feminism. Divergent Novel (2011) analyzed with reference to two points: the first is based on the analysis of structural elements, and the second is the analysis of motherhood by using the theory of feminism. This research use descriptive qualitative approach. This study uses two sources of data, namely, the first is a novel Divergent (2011) by Veronica Roth as a primary source. The second data source is the search of a book, a biography of the author, journal, sources that are directly related to the research. Two types of data obtained through the library were analyzed using descriptive analysis. Based on these studies, researchers concluded some conclusions. The first is a novel structural element obtained through the haracters and characterization, setting the place and time, plot, point of view, and the theme is structured into one as the story in the novel. The second is based on the theory of feminism in woman's participation, woman's role, women's rights, and woman's position that occurred on the main character and the other characters in the Divergent novel (2011). Keywords: Motherhood, Structural Elements Novel, Feminist Theory